Die Analyse von Calciumspuren im Gallium mit Hilfe der Isotopenverdünnungsmethoden - P. Lerch; C. Vuilleumier (CHIMIA)
With the help of isotopic dilution method it was possible to follow with great sensibility the comportment of the calcium during the purification processes of metallic gallium. The calcium-45 was added to alkaline solution of gallate. The electrolyse of this solution gives different amounts of calcium in gallium according to its initial concentration. The acid-treatment of the gallium allowed its subsequent purification and diminishes the amount of calcium.